2014
DOI: 10.1093/omcr/omu046
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Sarcina and Giardia in a child

Abstract: We present a case of 3-year-old boy who presented with vomiting and chronic diarrhoea, and the duodenal biopsy showed the presence of both Giardia and Sarcina. The clinical and pathological significance of Sarcina remains unknown in human beings and its co-existence with Giardia has not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Coinfection of S. ventriculi with Giardia , Helicobacter pylori , and Candida has been rarely reported . Our patient also harbored coexistent Candidiasis with S. ventriculi .…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Coinfection of S. ventriculi with Giardia , Helicobacter pylori , and Candida has been rarely reported . Our patient also harbored coexistent Candidiasis with S. ventriculi .…”
Section: Discussionmentioning
confidence: 53%
“…In this case, chronic gastritis was noted. S. ventriculi has also been reported as an incidental finding in patients of hepatitis and adenocarcinoma …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this report the diagnosis was based on morphological findings, and was not carried out the bacterial isolation. In previous studies in animals and humans the histology and cytology methods have been often used because bacteria of Sarcina genus have an unique morphological feature that is not found in other agents, as well as its extremely difficult isolation of which in most cases revealed negative results (DEBEY et al, 1996;VATN et al, 2000;EDWARDS et al, 2008;KUMAR et al, 2014;BHAGAT et al, 2015;SOPHA et al, 2015). In a previous study, 67 lambs with abomasal disease (abomasal bloat or rupture) and 45 healthy lambs were analyzed histopathologically, and the study found bacteria of the Sarcina genus in the abomasum of 53 lambs with abomasal disease and the absence of this bacteria in the abomasum of healthy lambs, demonstrating a possible causal association between bacteria from the Sarcina genus and gas accumulation in the abomasum.…”
Section: Timpanismo Abomasal Associado a Bactérias Do Gêneromentioning
confidence: 99%
“…The first case from India was reported by Louis et al . Following this, three successive reports of Sarcina in gastric aspirate, duodenal biopsy and lung resection were documented in India . This is possible due to the awareness among the surgical pathologists rather than an actual resurgence of Sarcina that has resulted in the recent publication surge.…”
Section: Discussionmentioning
confidence: 99%